Out of the burning house : political socialization in the age of affluence - Hobbs, Sandy (Cambridge Scholars Pub., 2011)
This unique collaboration, between a Marxist historian and behaviourist psychologist, is a vivid picture of the cultural milieu they experienced at Aberdeen University, and of social forces often overlooked in histories of the time: Scientific Humanism, The New Left, and precursors of the Women's Liberation Movement. As students together in the MacMillan Era, they shared an attachment to socialist, secular and scientific values. Like Brecht, they saw those unwilling to commit to revolutionar ...